Noninvasive stimulation of the temporoparietal junction: A systematic review. (August 2015) - Donaldson, Peter H.; Rinehart, Nicole J.; Enticott, Peter G.
Highlights: We review all noninvasive stimulation studies modulating TPJ activity. Methodological limitations, strengths and potential improvements are highlighted. The existing and potential clinical applications of TPJ stimulation are explored. Relevance to theoretical models of TPJ functional anatomy is discussed. Alternative account unifying attention, self/other and mentalising processes posited. Abstract: Imaging and lesion studies have suggested numerous roles for the temporoparietal junction (TPJ), for example in attention and neglect, social cognition, and self/other processing. These studies cannot establish causal relationships, and the importance and relevance of (and interrelationships between) proposed roles remain controversial. This review examined studies that use noninvasive transcranial stimulation (NTS) to explore TPJ function. Of the 459 studies identified, 40 met selection criteria. The strengths and weaknesses of NTS-relevant parameters used are discussed, and methodological improvements suggested. These include the need for careful selection of stimulation sites and experimental tasks, and use of neuronavigation and concurrent functional activity measures. Without such improvements, overlapping and discrete functions of the TPJ will be difficult to disentangle. Nevertheless, the contributions of these studies to theoretical models of TPJ function are discussed, and the clinical relevance of TPJ stimulation explored. Some evidence exists for TPJ stimulation in the treatment of auditory hallucinations, tinnitus, and depersonalisation disorder. Further examination of the TPJ in conditions such as autism spectrum disorder is also warranted.